2020
DOI: 10.1371/journal.pntd.0008447
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional complementation of ten Schistosoma mansoni phosphodiesterases expressed in the mammalian host stages

Abstract: Only a single drug against schistosomiasis is currently available and new drug development is urgently required but very few drug targets have been validated and characterised. However, regulatory systems including cyclic nucleotide metabolism are emerging as primary candidates for drug discovery. Here, we report the cloning of ten cyclic nucleotide phosphodiesterase (PDE) genes of S. mansoni, out of a total of 11 identified in its genome. We classify these PDEs by homology to human PDEs. Male worms displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…After cloning the SmPDE4a gene [ 26 ], we set out to characterize this parasite PDE biochemically, pharmacologically, as well as structurally to enable a structure-based drug design program aiming to target SmPDE4A. To this end, two 6×His-tagged SmPDE4a constructs were generated, PCR amplified and cloned into pOPINF encoding a cleavable N -terminal 6×His tag.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After cloning the SmPDE4a gene [ 26 ], we set out to characterize this parasite PDE biochemically, pharmacologically, as well as structurally to enable a structure-based drug design program aiming to target SmPDE4A. To this end, two 6×His-tagged SmPDE4a constructs were generated, PCR amplified and cloned into pOPINF encoding a cleavable N -terminal 6×His tag.…”
Section: Resultsmentioning
confidence: 99%
“…Within the EU-funded consortium PDE4NPD aiming at investigating the potential of parasite PDEs as drug targets, we decided at its start in 2014 to embark on a PDE target discovery program for S. mansoni [ 25 ]. Munday et al [ 26 ] identified 11 different PDE open reading frames in the S. mansoni genome and cloned 10 of these SmPDEs (ranging from 517 to 1081 amino acids) from cDNA. Moreover, using different expression systems (yeast, T. brucei ), enzymatic activity was documented for six of the SmPDEs [ 26 ], making these parasite PDEs attractive new drug targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we expressed in S. pombe PDE4, PDE8, and PDE11 family members from the blood fluke Schistosoma mansoni , whose genome includes members of all 11 Class I PDE families ( Vyas et al, 2021 ). 5FOA growth assays were used to determine the relative ability of these enzymes to hydrolyze cAMP and cGMP as shown by an increase in amount of exogenous cNMP required to confer 5FOA R growth ( Munday et al, 2020 ). However, an even more fertile area of research could involve the treatment of infections by parasitic nematodes due to the existence of the well-established model organism nematode Caenorhabditis elegans ( Corsi et al, 2015 ), whose genome includes only six Class I PDE genes.…”
Section: Targeting Parasitic Nematode Pdesmentioning
confidence: 99%